Cardless banking system in Malaysia: An extended TAM - Qaisar Ali; Shazia Parveen; Hakimah Yaacob; Zaki Zaini (Risks, 2021)
The main objective of this study is to analyse consumers' behavioural intentions to use cardless banking technology in Malaysia. The intentions to use this technology are evaluated through an extended Technology Acceptance Model (TAM) framework. The data were collected from 447 Maybank and Hong Leong Bank customers in Selangor and Kuala Lumpur. The results show that self-efficacy (SE) had a positive impact on the perceived ease of use (PEOU), while perceived risk (PR) had a negative impact on perceived usefulness (PU) and intention to use (IU) cardless banking. Next, the perceived ease of use (PEOU) had a positive impact on perceived usefulness (PU). The results further support the idea that perceived usefulness (PU) and perceived ease of use (PEOU) had the strongest impacts on intention to use (IU). The practical implications of this study suggest that developers of cardless banking technology should introduce secure, less complicated, and easily accessible technology to improve consumers' intentions to use. The perceived usefulness of this technology can be improved through promotional strategies and consumer training. Theoretically, this study has successfully extended TAM in the context of cardless banking technology in Malaysia. Moreover, this study will assist bankers in designing effective marketing strategies to attract more customers, which will add significant value to the overall business of the banking industry.
Keywords: 330; cardless banking; customer intention; fraud protection; Malaysia; TAM